Analysis of Potential Tourism Attractions in Manado City - Tangian, Diane; D. Polii, Bernadain; M.H. Mengko, Seska (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
The tourism industry is currently experiencing significant progress as can be seen from the number of annual tourist visits that has increased. The number of tourists visiting the city of Manado in 2015 was 1,103,081 tourists, in 2016 it was 1,531,505 and in 2017 it increased to 1,786,499 tourists. The increased number of tourist visits will certainly have a positive impact on economic growth and social welfare. The tourism industry is said to be successful if the number of tourist visits increases. With the increase in the number of tourist visits, the economy and welfare of the people will also increase. The longer tourists stay, the more money they spend on shopping. Seeing the potential of the tourism industry, it is necessary to identify the existing potential objects and tourist attractions so that tourists who visit have a variety of tourist attractions offered. In addition, it is also to maintain the environmental sustainability of Bunaken tourism objects from the pressure of the number of tourist visits that exceeds the carrying capacity limit. The utilization of the potential objects and tourist attractions, starting from natural, artificial, historical, artistic and cultural tourism must be carried out optimally. The assessment of the potential of the tourist objects and attractions is carried out by using the table of assessment criteria for potential objects and natural attractions of the Department of Forestry.